2018
DOI: 10.5387/fms.2018-02
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapy according to next generation sequencing-based panel sequencing

Abstract: Targeted therapy against actionable gene mutations shows a significantly higher response rate as well as longer survival compared to conventional chemotherapy, and has become a standard therapy for many cancers. Recent progress in next-generation sequencing (NGS) has enabled to identify huge number of genetic aberrations. Based on sequencing results, patients recommend to undergo targeted therapy or immunotherapy. In cases where there are no available approved drugs for the genetic mutations detected in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…In our study, 23 EGFR mutated patients received second-line liquid biopsy a er the failure of first-generation of Since its introduction in 2007, NGS technology has already made extraordinary advances, making the detection of genetic alterations to guide therapy to be more feasible. And as NGS becomes faster and less expensive, it's sure to be used more frequently and with greater benefit for Chinese NSCLC patients [15]. In our real-world data, 83.33% patients chose NGS-guided targeted therapy in first-line and/or second-line therapy.…”
Section: Discussionmentioning
confidence: 90%
“…In our study, 23 EGFR mutated patients received second-line liquid biopsy a er the failure of first-generation of Since its introduction in 2007, NGS technology has already made extraordinary advances, making the detection of genetic alterations to guide therapy to be more feasible. And as NGS becomes faster and less expensive, it's sure to be used more frequently and with greater benefit for Chinese NSCLC patients [15]. In our real-world data, 83.33% patients chose NGS-guided targeted therapy in first-line and/or second-line therapy.…”
Section: Discussionmentioning
confidence: 90%
“…Next generation sequencing-based panel sequencing is currently used in daily clinical practice, which could improve the detection of ARID1A mutations in various cancers as well as in GC [31]. In this study, since ARID1Adeficient GC cells are shown to be sensitive to EZH2 inhibitors, a synthetic lethality approach with EZH2 inhibitors should be considered as an additional therapeutic strategy for ARID1A-dificient GC.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of new molecular targets and the availability of modern immunotherapeutic approaches have revolutionized the treatment of advanced melanoma. By enabling the detection of genomic, transcriptional and epigenetic changes, NGS has allowed the identification of specific targets, thereby allowing for the development and optimization of treatments interfering with specific molecular targets [ 10 , 11 ]. Although such novel therapeutic approaches have demonstrated clinical efficacy and rapid responses in most patients, acquired resistance represents a significant challenge and has yet to be overcome.…”
Section: Melanoma Targeted Therapy and Immunotherapy: An Overviewmentioning
confidence: 99%